Numerical investigation into the effects of corrosion on the shear performance of pretensioned bridge girders with cast-in-place slabs. (December 2022) - Jadwiga Osmolska, Magdalena; Kanstad, Terje; Hendriks, Max A.N.; Markeset, Gro
Abstract: Corrosion and shear cracking are frequently observed near supports of pretensioned bridge girders in coastal climates, so non-linear finite element analysis was used to study the effect of corrosion on shear performance in a real case study. Varying degrees of corrosion and various locations (top strands, bottom strands, vertical stirrups and girder-slab interface) were considered. The analyses included construction phases, concrete creep and shrinkage, and the effects of corrosion on the properties of prestressing and reinforcing steel, concrete, and the bond between concrete and reinforcement. The study shows that high (20%) corrosion in the bottom layer of strands can modify the failure mode from concrete crushing in the web to strand slippage or crushing of concrete in the support zone with limited cracking. Although severe strand corrosion significantly compromises girder capacity and ductility, failure occurs only when there is overloading. The predicted failure mode was also sensitive to material parameters, in particular the corrosion-induced crack widths used for modelling the reduced concrete strength. Nevertheless, some similarities were noticed between observed and predicted cracking occurrence. For moderate corrosion (10%), girder capacity was limited by strand fracture, but extensive flexure and shear cracking would appear before failure. 20% corrosion in the vertical stirrups in the web seems to have potentially smaller effect on the shear capacity than 20% corrosion in the strands in support, while corrosion in the top strands or stirrups in the girder-slab interface did not affect the girder capacity.